IDENTIFIKASI JENIS DAN HABITAT JAMUR MAKROSKOPIS DI HUTAN LARANGAN ADAT RUMBIO KABUPATEN KAMPAR PROVINSI RIAU - Nasution, Fadlan; Rahayu Prastyaningsih, Sri; Ikhwan, Muhammad (Fakultas Kehutanan Universitas Lancang Kuning, 2018)
The purpose of this study is to identify the types of Macroscopic Mushroom and Know the habitat of Macroscopic Fungi in Forest Area Prohibition of Rumbio Adat, Kampar regency of Riau Province.jamur using exploratory method with purposive sampling technique. The data obtained then analyzed by descriptive-explorative method. Based on the results of research that has been done in the forest area of ​​Rumbio Indigenous Ban found 30 types of Macroscopic mushrooms from 1 Division Basidiomycota namely, Amaroderma sp, Calocera cornea, Clytocybe sp, Collybia sp, Collybia sp1, Coltricia perennis, Coltricia cinnamomea, Crepidotus variabilis, Crepidotus herbarum, Coriolopsis Occidentalis, Daedinella sp, Fomitopsis pinicola, Fomes fomentarius, Fomes lignosus, Ganoderma sp, Ganoderma sp1, Hygrocybe miniata, Hydnellum sp, Lepiota cristata, Lepiota atrodisca, Lignosus rhinocerus, Marasmius andrasaceus, Marasmius foetidus, Marasmiellus sp, Mycena sp, Polyporus sp, Polyporus sp1, Piptoporus betulinus, Ramariopsis kunzei, Schlzophyllum commune. The types of fungi found in this study are divided into 6 Order and 12 Family. The Order of Agaricales is the dominant group in the study site, since the number of families and species is most widely found in this study. The environmental conditions of the study sites are temperature 24-310C, air humidity 75-89%, light intensity 125-1226 lux and soil pH 5.5-6,4.